Pemodelan Sistem Tata Kelola Pengetahuan Perguruan Tinggi Penunjang Proses Akademik (Studi Kasus: Fakultas Teknologi Informasi Universitas Atma Jaya Makassar) - Adi Chandra Syarif (TEMATIKA: Jurnal Penelitian Teknik Informatika dan Sistem Informasi, 2022)
Knowledge has become an important asset, capital and resource in organizations. This is especially true for a higher education institution. Higher education institution can be said to be an organization whose assets are dominated by knowledge, whether it is attached to the teachers (which are tacit) or codified. Tacit Knowledge and explicit knowledge in the academic process owned by the Faculty of Information Technology Atma Jaya Makassar University has not stored and managed properly. This research focus on how to design a model of Knowledge Management System in the academic process so that model becomes a picture of the KMS in accordance with the needs of FTI to manage their knowledge and the design results of KMS model can be implemented in the future. The result of this research is a prototype of Knowledge Management System model in the academic process for FTI.Explicit,